Cultural Values and Retail Investor Behavior under Market Volatility: A Cross-Country Panel Analysis (2002–2021) - Luz Maria Sipi Chevola; Xie Yamin (European Scientific Journal, ESJ, 2026)
This study examines how national culture influences financial market development and volatility across 18 countries from 2002 to 2021. Integrating Hofstede’s cultural dimensions, particularly Uncertainty Avoidance (UAI) and Individualism (IDV), with market indicators such as capitalization, trading volume, and turnover, the analysis explores how socio-cultural factors interact with global risk conditions measured by the VIX index. Using fixed-effects and dynamic panel regressions, the results show that higher individualism is associated with deeper and more liquid markets, while greater uncertainty avoidance constrains trading intensity but supports more stable capitalization. Global volatility negatively affects liquidity, yet its impact is moderated by cultural characteristics, with stronger effects observed in emerging economies. These findings highlight that financial development is not purely institutional or macroeconomic but also culturally embedded. The study underscores the importance of tailoring financial policies to societal norms to enhance market efficiency and resilience amid global uncertainty.